Gut hormones and Type 2 diabetes mellitus. (October 2014) - Falinska, Agnieszka M; Tan, Tricia; Bloom, Stephen
SUMMARY : Type 2 diabetes mellitus (DM2) is a global threat to health with numbers of cases increasing exponentially. The pharmacological agents currently available for treatment of DM2 do not result in disease remission. Strikingly, bariatric surgery is successful in enforcing a prolonged remission of DM2 in a proportion of patients. The gut releases several hormones upon feeding, which affect hypothalamic, vagal and enteropancreatic pathways involved in the regulation of satiety and metabolism. One of the principal mechanisms by which bariatric surgery is capable of ameliorating DM2 is by means of increasing the secretion of key gut hormones such as glucagon-like peptide-1 (GLP-1), oxyntomodulin (OXM) and peptide YY (PYY). This review discusses available DM2 treatments based on GLP-1, as well as the potential therapeutic role of other gut hormones such as OXM, glucose-dependent insulinotropic polypeptide, ghrelin and PYY.